2013
DOI: 10.4028/www.scientific.net/amm.332.44
|View full text |Cite
|
Sign up to set email alerts
|

Morphing Wing Concept for Small UAV

Abstract: The biological flight involves the movement of a wing (lift surface) in viscous medium and it generates lift and resistance for going forward through friction compared to Reynolds number. The morphing concept is generally based on optimizing the aerodynamic form during the mission so it can execute a maneuver flight. This article desires a short passage through the mathematical aspect in 2D of the morphing profile concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…13) indicate a reduced dependence on the lateral stability of the geometric configurations influenced by the use of the four analyzed profiles, the net differences increase with the increase in the incidence of flight. Starting from the 2D profile approach, the morphing concept can be used to construct 3D lifting surfaces, especially for maneuvering by adaptive control [10,11,12], both using morphing profiles (FIG. 15) and 3D wing torsion (FIG.…”
Section: Figmentioning
confidence: 99%
“…13) indicate a reduced dependence on the lateral stability of the geometric configurations influenced by the use of the four analyzed profiles, the net differences increase with the increase in the incidence of flight. Starting from the 2D profile approach, the morphing concept can be used to construct 3D lifting surfaces, especially for maneuvering by adaptive control [10,11,12], both using morphing profiles (FIG. 15) and 3D wing torsion (FIG.…”
Section: Figmentioning
confidence: 99%
“…Rapid and controlled modeling of the aperture and wing geometry can also be used to actively control some undesirable phenomena such as airplane detachments at low attack angles, or the occurrence of wing-induced aero-elastic loads, see Figure 5. Changing the shape and profile of a wing for different types of mission has been the subject of extensive studies reported in the literature [11,12,13,14].…”
Section: Future Development Trendsmentioning
confidence: 99%
“…Remotely piloted aircraft first appeared during world war I, but the early efforts were stymied by the primitive guidance technology available. NASA (Kudva, J. et al, 1997), DARPA (Kudva, 2004)and also most of researchers (Abdulrahim et al, 2005;Bourdin, Gatto and Friswell, 2006;Gomez and Garcia, 2011;Prisacariu, Boscoianu and Cîrciu, 2013;Kaygan and Gatto, 2016;Prisacariu, Boşcoianu and Cîrciu, 2017) have been conducted performance studies regarding unpiloted morphing aerial vehicles. (Abdulrahim et al, 2005) designed twist morphing wings and flight tests demonstrate the actuation causes sufficient deformation of the wing to result in significant control authority.…”
Section: Introductionmentioning
confidence: 99%